Resíduos sólidos no sistema de drenagem urbana na bacia do arroio Tamandaí em Santa Maria - RS - Gonçalves, Ígor Hofstadler Peixoto (2013)
With population growth, and the resulting increase in urbanization, the disposal of solid waste in water bodies in Brazil has increased in recent years, especially in the outskirts of the cities. These residues, along with the waste drainage system tributary, are transported by the stream, causing the siltation of its bed, and frequent overflows, as well as contamination of soil and water. Within this context, it was mounted on a stream a structure for urban solid waste collection in a stretch of Cancela - Tamandaí s watershed in Santa Maria - RS. The structure was developed and adapted to the circumstances and location. In this work were quantified and qualified solid waste present in urban drainage of Santa Maria RS according to the CONAMA Resolution n.º 275/2001 and related to data of rainfall. The results concerning the monitoring structure were satisfactory, as the waste was retained in most rainfall events effectively. Were collected in total 1153.2 kg of solid waste in three months of collection with a rainfall total for the period of 518.94 mm, 93.9% of these being composed of organic matter, the same consisting of the expressive value of 86.0% of vegetation debris. The inorganic matter found is composed mostly of plastic (2.5%). Processed wood was also significant, representing 7.8 % of total quantified. Cancela Tamandaí s watershed presented a load of solid waste equal to 17.27 kg/ha/year or 0.424 kg/inhab./year, different from watersheds studied by Salles (2010) and Brites (2005), however the differences are related to the characteristics of each watershed. The prediction curve of drained solid waste is a parameter for decision to municipal managers in relation to solid waste generated within the Cancela - Tamandaí s watershed, because it relates the drained solid waste carted due to rainfall. The results demonstrate the significant environmental impact represented by the society against the inadequate disposal made by them. An environmental education program associated with measures for solid waste management would form the basis for the solution of this vast urban problem.